Closure of large bore 9 F arterial puncture sites with the AngioSeal STS device in acute stroke patients after intravenous recombinant tissue plasminogen activator (rt-PA). (15th May 2018) - Janssen, Hendrik; Killer-Oberpfalzer, Monika; Lange, Ruediger
Abstract : Purpose: This retrospective analysis was performed to evaluate whether large bore 9 F puncture sites can be safely closed with the 8 F AngioSeal STS device after endovascular stroke procedures in patients who did or did not receive recombinant tissue plasminogen activator (rt-PA). Methods: Out of 161 consecutive endovascular stroke procedures we identified 72 patients who met the inclusion criteria, of whom 46 received rt-PA before the endovascular procedure and 26 did not. All groin complications such as major haemorrhage, failure of the device to close the puncture site, delayed haemorrhage, acute lower extremity ischaemia or necessary vascular surgery as well as infections were recorded. Results: Only one patient had delayed groin haemorrhage after closure of the 9 F puncture site with the AngioSeal STS device. There was no significant difference in complications between patients with or without rt-PA treatment. Conclusion: The 8 F AngioSeal STS seems to be safe and efficient to close 9 F femoral artery puncture sites, even under active rt-PA thrombolysis.